Dr. Fanny Ballieux — Deep Plane Facelift — Brussels - Ballieux, Fanny (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Fanny Ballieux, practicing in Brussels, Belgium. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003329; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; belgium; brussels